Limited PSA testing in indigent men in South Texas: An appropriate care or missing a prevention opportunity? - Liang, Yuanyuan (2012)
BACKGROUND: No previous study has examined racial-ethnic differences in prostate specific antigen (PSA) testing and follow-up in primary care practices serving an indigent population. METHODS: From electronic medical records of primary care practices affiliated with one health care system in San Antonio, we identified 9,267 men aged 50–74 with 2+ clinic visits from 2008 through 2010 and no prior prostate cancer diagnosis. Logistic regression was used to examine the association of race-ethnicity with the use of PSA testing and, if tested, with an abnormal result (≥4 ng/mL) adjusted for demographics, health care and clinical factors. Time to a follow-up activity after an abnormal PSA was assessed using Cox proportional models. RESULTS: The race-ethnicity of this cohort was 63% Hispanic, 27% non-Hispanic White, 7% African-American, and 3% other. In a 3-year period, 26.8% of men had at least one PSA test. Compared with African-Americans, non-Hispanic Whites were less likely to be tested (OR=0.68; 95% CI:0.55,0.83) but Hispanics did not differ (OR=0.95; 95% CI:0.79,1.15). African-Americans were more likely to have an abnormal PSA than others (12.4% versus 5.2%, p<0.001) and the shortest adjusted time to follow-up (p=0.004). CONCLUSIONS: In this 3-year indigent cohort, about one quarter had a PSA test, approximately half of the national testing rate. IMPACT: African-Americans were more likely to be tested than non-Hispanic Whites but had more abnormal results, raising concerns about missed prevention opportunities. African-Americans with high PSA results had the shortest time until follow-up, reflecting awareness of the threat of prostate cancer for African-Americans by physicians.